2022
DOI: 10.3389/fncom.2021.678232
|View full text |Cite
|
Sign up to set email alerts
|

Neural Substrates of the Drift-Diffusion Model in Brain Disorders

Abstract: Many studies on the drift-diffusion model (DDM) explain decision-making based on a unified analysis of both accuracy and response times. This review provides an in-depth account of the recent advances in DDM research which ground different DDM parameters on several brain areas, including the cortex and basal ganglia. Furthermore, we discuss the changes in DDM parameters due to structural and functional impairments in several clinical disorders, including Parkinson's disease, Attention Deficit Hyperactivity Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 169 publications
(228 reference statements)
2
12
0
Order By: Relevance
“…CBGT circuits can control decision parameters under uncertainty. Both theoretical (9,12,14,(19)(20)(21) and experimental (18) evidence suggest that the CBGT circuits play a critical role in the evidence accumulation process (for a review see 36 (22)). The canonical CBGT circuit (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CBGT circuits can control decision parameters under uncertainty. Both theoretical (9,12,14,(19)(20)(21) and experimental (18) evidence suggest that the CBGT circuits play a critical role in the evidence accumulation process (for a review see 36 (22)). The canonical CBGT circuit (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…An advantage of applying the DDM was that many studies have examined the correspondence between DDM’s each parameter and neural substrate. It has been reported that the prefrontal cortex, frontal eye field, lateral intraparietal area, and medial prefrontal cortex effected drift rate parameter, and the subthalamic nucleus and pre-supplementary motor area effected decision threshold [ 44 47 ]. Recently, noninvasive brain stimulation on the dorsolateral prefrontal cortex has been reported to be effective as a smoking cessation treatment [ 48 ], and this stimulation site coincides with an area that is related to drift rate.…”
Section: Discussionmentioning
confidence: 99%
“…Although first described over 50 years ago, the DDM has recently enjoyed widespread use, partly due to the development of powerful and freely-available software implementing computationally-intensive model-fitting algorithms, and partly due to an accumulating literature documenting that the DDM can indeed shed light on latent cognitive processes that are not necessarily evident from traditional hypothesis-driven methods of behavioral data analysis (Deghan et al, 2022), and that have been linked to specific brain regions (Mulder et al, 2012;Mueller et al, 2017;Weigard and Sripada, 2021;Gupta et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the current article is not meant to offer a comprehensive review of the DDM literature (for good reviews, see, e.g., Forstmann et al, 2016;Ratcliff et al, 2016;Evans and Wagenmakers, 2020;Gupta et al, 2022), nor a general tutorial on good computational modeling practices (see, e.g., Daw, 2011;Heathcote et al, 2015;Wilson and Collins, 2019); however, it may provide a useful springboard for cognitive psychologists and neuroscientists considering the use of the drift diffusion model, and related computational models, in their own research.…”
Section: Introductionmentioning
confidence: 99%